Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,333 questions

17,804 answers

1,438 comments

35,281 users

find each function. a)(f.g)(x) b)(f-g)(x)

+3 votes

 

functions

   

f(x) = x ^2 + 5x - 1 and g(x) = 3x - 2, 

 

asked Jan 2, 2013 in ALGEBRA 2 by homeworkhelp Mentor

2 Answers

+3 votes

a) (f. g) (x)

Given fuctions f(x) = x ^2 + 5x - 1 and g(x) = 3x - 2,

= f(x). g(x)

= ( x ^2 + 5x - 1)(3x - 2)

= ( x ^2 + 5x - 1)(3x) - ( x ^2 + 5x - 1)(2)

= 3x^3 + 15x^2 - 3x - 2x ^2 - 10x + 2

= 3x^3 + 13x^2  - 13x + 2

answered Jan 2, 2013 by ashokavf Scholar
+3 votes

b)  (f - g)(x)

Given fuctions f(x) = x ^2 + 5x - 1 and g(x) = 3x - 2

= f(x) - g(x)

= x ^2 + 5x - 1 - (3x - 2)

= x ^2 + 5x - 1 - 3x + 2

= x ^2 + 2x + 1

answered Jan 2, 2013 by ashokavf Scholar

Related questions

...